EXTENSION PROGRAMS PLANNING UNDER COMPREHENSIVE QUALITY STANDARDS IN SOME MIDDLE PROVINCES OF IRAQ - & Naji, Al-zaidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The research aimed  to determine the overall quality standards through literature and specialists and overall quality experts , and to identifying the applied level by managers in some provinces of the central region . In order to achieve the objectives of the research , the researcher developed five scale ranging from grades ' ( 0-4 ) degree for the purpose of identifying the level of application of total quality standards for program planning by managers in the provinces of the central region , included (73) items distributed on (10) axes and ( 4) field (inputs , processes , outputs , feedback ) . The research was conducted on  a random sample of 50%  of Iraqi middle provinces ( Baghdad , Karblaa , Najaf , Wasit ) . A random sample about 39% of the agricultural divisions of these provinces of 20 agricultural divisions were chosen . The sample of  respondents was 96 , 7 of them ( general manager , two assistants of the general manager and heads of the technical departments) were in department of agricultural extension  and training , 15 of them ( the managers of agricultural directorates and the heads of agricultural extension and Heads of departments of planning in those offices) , 60 of them person ( heads of agricultural divisions  and the officials of the units of agricultural extension  and planning ), 4 of them  ( managers of  extensional  training centers ) 10 of them of extension farms officials  in the chosen research  provinces . Results have showed that the level of application of total quality standards for planning and agricultural extension programs by managers in some provinces of the central region , by (50% )  The researcher recommende the adoption of the search results by the Ministry of Agriculture/  Planning Department to improve the agricultural extension programs  planning process : Also the researcher recommended the need to review budgets and financial measures to ensure the provision of the necessary work indicative items on time , and its importance that the extension organization has independent operational budget on all levels , and to be distributed to the terms and aspects of exchange of field activities.